Care at a Distance (2012)
This widely researched study demonstrates convincingly that neither grandiose promises nor nightmare scenarios have much to do with actual care practices employing telecare. Combining detailed ethnographic studies of nurses and patients involved in telecare with a broad theoretical frameworky from various disciplines, the author concludes that these practices leads to more rather than less intense caring relations, resulting from a spectacular raise in the frequency of contacts between nurses and patients. Patients are much taken with this, not because they feel they are finally able to manage themselves, but because they can ‘leave things to the experts’. The patients find that caring is something that is best done for others. The book frames urgent questions about the future of telecare and the ways in which innovative care practices can be built on facts rather than hopes, hypes or nightmares.